Connectivity of Accreditation Instrument Strengthening Policy in Realizing Excellent Primary and Secondary Education Services in Banten Province - Jumanah, Jumanah; Nugroho, Arif; Ratnasari, Dine Trio (Jurnal Manajemen Pelayanan Publik, 2025)
This study examines the policy connectivity of strengthening accreditation instruments in relation to efforts to realize quality education services at the primary and secondary levels in Banten Province. Employing a qualitative approach with a case study method, the research involved informants from local government officials, BAN-S/M assessors, school principals, teachers, supervisors, school committees, and parents. The findings reveal that although the School Accreditation Instrument (IASP 2020) has been introduced, its integration into regional education planning, budgeting, and supervision remains limited. Some schools are able to translate accreditation indicators into quality management practices, yet the majority face challenges related to understanding, inter agency coordination, and follow up on accreditation results. Additional inhibiting factors include the absence of a formal coordination mechanism between BAN-S/M and the Education Office, as well as the lack of technical policies at the regional level. This study highlights the importance of cross level policy connectivity as a prerequisite for strengthening accreditation, an issue that has been rarely explored in previous studies. The recommendations emphasize synchronizing national and regional policies, enhancing the capacity of education personnel, and formulating operational regulations at the regional level to ensure that accreditation functions effectively as an instrument for improving the quality of education services.